2017
DOI: 10.1016/j.ijnurstu.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early psychological symptom severity on long-term functional recovery: A secondary analysis of data from a cohort study of minor injury patients

Abstract: Background The mental health consequences of injuries can interfere with recovery to pre-injury levels of function and long term wellbeing. Objectives The purpose of this study was to explore the relationship between psychological symptoms after minor injury and long-term functional recovery and disability. Design This exploratory study uses secondary data derived from a longitudinal cohort study of psychological outcomes after minor injury. Setting Participants were recruited from the Emergency Departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…This highlights the urgent need for interventions that initiate and extend a continuity of longterm engagement with tools like mobile health monitoring. Similar to the limited corpus of research on long-term outcomes after trauma, we found that many patients in this pilot study continued to express signs and symptoms of poor recovery and chronic injury sequalae months and years after their hospitalization (13,15,(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 75%
“…This highlights the urgent need for interventions that initiate and extend a continuity of longterm engagement with tools like mobile health monitoring. Similar to the limited corpus of research on long-term outcomes after trauma, we found that many patients in this pilot study continued to express signs and symptoms of poor recovery and chronic injury sequalae months and years after their hospitalization (13,15,(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 75%
“…F. Zatzick et al 2004). These symptoms present significant challenges to the restoration of social and familial roles, ability to work, and quality of life after injury (Holbrook et al 1998; Vles et al 2005; Richmond et al 2009; Jacoby, Shults, and Richmond 2017)…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we focused on severity of psychological symptoms rather than DSM-5 diagnoses. Based on previous work by our group, post-injury psychological symptom severity is associated with suboptimal recovery after injury [23].…”
Section: Discussionmentioning
confidence: 99%